AN APPROACH TO CELL NUCLEI COUNTING IN HISTOLOGICAL IMAGE ANALYSIS - M. M. Lukashevich; V. V. Starovoitov (Системный анализ и прикладная информатика)
In the paper a method of automatical counting the number of cell nuclei in histological images is studied. This operation is commonly used in the diagnostics of various diseases and morphological analysis of cells. In this connection, the procedure of automatical count the number of cell nuclei is a key step in the systems of medical imaging microscopic analysis of histological preparations. The main aim of our work was to develop an efficient scheme of automatic counting cell nuclei based on advanced image processing methods: directional filtering, adaptive image binarization and mathematical morphology. Unlike prior research, the presented approach does not provide segmentation of cell nuclei in the image, but only requires to detect them and count their number. This avoids complex algorithmic calculations and provides good accuracy of counting cell nuclei.The paper describes a series of experiments conducted to assess the effectiveness of the proposed method using the available online database of medical test histological images. Critical parameters defined algorithms, configurable at each stage of image analysis. For each parameter we have defined value ranges, and then realized a selection of optimal values for every parameter and a mutual combination of them. It is based on generally accepted quantitative measures of precision and recall. The results were compared with the state-of-art investigations in this field and demonstrated an acceptable level of accuracy of the proposed method. The software prototype developed during the study can be regarded as an automatic tool for analysis of cell nuclei. The presented approach can be adapted to various problems of analysis of cell nuclei of various organs.